Sintesis dan Uji Aktivitas Senyawa Dibutil Timah (IV) Bis-Metil Ditiokarbamat Pada Bakteri Salmonella Typhi dan Escherichia Coli - Mukhlis Sanuddin; lia purnamasari; Amelia Soyata (Jurnal Farmasi Indonesia, 2022)
The majority of bacterial infection therapy uses antibiotics which result in resistance and dangerous side effects. If the wrong method is used, it is necessary to develop antibiotics from new compounds that are effective against bacteria and are able to avoid the occurrence of antibiotic resistance by using organotin and dithiocarbamate compounds. The purpose of this study was to determine the antibacterial activity of dibutyl tin (IV) bis-methyl dithiocarbamate on Salmonella typhi and Escherichia coli bacteria. This compound was synthesized by an in situ technique by adding methanol to methyl amine + carbon disulfide + metal dibutyl tin (IV) dichloride which was identified using 13C NMR, FTIR and 1H NMR. Then, the antibacterial activity was tested using the paper disc diffusion technique with concentrations of 50 ppm, 70 ppm and 90 ppm using NA (Nutrient Agar) media. The results of this study obtained results in the form of a synthetic powder of 1.28 g with a compound percentage of 25%. The results of the antibacterial activity test with a concentration of 90 ppm resulted in the largest inhibition zone with a very strong category at 27.33 mm Salmonella typhi and 26.48 mm Escherichia coli. The compounds in this research have been successfully synthesized and form an overview of the structure of complex compounds and have very strong antibacterial agent activity.